In vitro transcription of a human hsp 70 heat shock gene by extracts prepared from heat-shocked and non-heat-shocked human cells. - Drabent, B (1986)
A cDNA clone homologous to HeLa cell mRNA encoding the 70 kDa human heat shock protein (hsp 70) was used to isolate a recombinant phage containing an entire human hsp 70 gene. Sequence analysis of the 5' and 3' flanking regions revealed the structural integrity of the regulatory elements. The functional integrity of this hsp 70 gene was substantiated by in vitro transcription studies with nuclear extracts. Specific run-off transcripts, synthesized by RNA polymerase II, were obtained with extracts prepared from heat-shocked cells. Extracts from non-heat-shocked cells were found inactive in hsp 70 gene transcription. However, 5' deletion mutants lacking the heat shock element (HSE) were transcribed by both heat shock and nonheat shock HeLa extracts.